Activities of living of disabled people according to the Roper-Logan-Tierney model of nursing - Gisele Nogueira de Moura; Jennara Candido do Nascimento; Maria Alzete de Lima; Natasha Marques Frota; Vicente Matias Cristino; Joselany Áfio Caetano (Universidade Federal do Ceará, 2015)
Objective: to identify the activities of living of disabled people by applying the Roper-Logan-Tierney Model of Nursing. Methods: cross-sectional study conducted in private university. The population comprised 13 people with physical and sensory disabilities, who practiced water sports. Data collection occurred through structured script. Results: most participants came from the capital, were male, aged between 19 and 69 years. The most affected activities of living were Maintaining a safe environment, Mobilization, and Sleeping. There were 15 nursing diagnoses related to each activity identified, in addition to the expected outcomes and interventions. Conclusion: the model of living enabled to identify the group's limitations in carrying out activities of living, constituting a fertile field for nursing actions.